Cleaning as high-risk activity for respiratory particulate exposure during additive manufacturing of sand moulds and its preceding silica sand coating process - Matlhatsi, Ntoko Lucas; du Preez, Sonette; Van Der Merwe, Cornelius J; Linde, Stephanus J L (Annals of work exposures and health, 2025)
Occupational exposure to respirable crystalline silica (RCS) is a known cause of respiratory diseases, such as silicosis and lung cancer. Binder jetting additive manufacturing (AM) uses silica sand coated with sulphonic acid as feedstock material and operators are potentially exposed to RCS during various activities associated with AM. This includes the cleaning of the AM machine and associated equipment. This study aimed to investigate particulate exposures associated with additive manufacturing of sand moulds and its preceding silica sand coating process. The particle size distribution (PSD) and particle shape analysis of different forms of silica sand (virgin, coated, and used) was determined using a Malvern Morphologi G3 automated microscope and the structural characteristics was measured using X-ray diffraction (XRD). Personal exposure and area monitoring for airborne respirable dust and RCS were performed using MDHS 14/4 and NIOSH 7602, while real-time particle number concentrations of 0.3 to 10 µm sized particles was measured using the TSI Aerosol Particle Counter (APC). Monitoring was performed for 2 operators over 8 d and included 3 d of coating, one day of cleaning the AM machine, and 4 d of printing during which 3 identical parts were manufactured. According to the PSD analysis, virgin and used silica sand particles were mostly in the respirable size range (d(0.9) = 3.98 ± 0.72 µm; and d(0.9) = 6.51 ± 2.71 µm, respectively), while coated sand was mostly in the inhalable size fraction d(0.5) = 29.76 ± 42.91 µm). The wt% results of the XRD analysis for the bulk virgin, coated and used silica sand were 97.3%, 92.6%, and 96.8% quartz, respectively. Personal exposure to RCS exceeded the exposure limit of 0.1 mg/m3 when the operator used compressed air to clean the coating machine's filter (0.112 mg/m3) and exceeded the action level on the day the AM machine was cleaned (0.70 mg/m3). The results for real-time particle number concentrations of 0.3 to 10 µm sized particles showed peaks while the cleaning activities such as dry sweeping were performed. The personal exposure to RCS was the highest on days when cleaning activities that used compressed air and dry sweeping took place. The high quartz content of the silica sand feedstock material and the respirable size of the virgin and used silica sand particles means that cleaning activities pose an RCS exposure risk to AM operators. Nine recommendations are made to reduce exposure to RCS during cleaning activities.